Greek medicine from Hippocrates to Galen : selected papers - Jouanna, Jacques (Studies in ancient medicine, 2012)
This volume makes available for the first time in English translation a selection of Jacques Jouanna's papers on medicine in the Graeco-Roman world. The papers cover more than thirty years of Jouanna's scholarship and range from the early beginnings of Greek medicine to late antiquity. Part One studies the ways in which Greek medicine is related to its historical and cultural background (politics, rhetoric, drama, religion). Part Two studies a number of salient features of Hippocratic medicine, such as dietetics, theories of health and disease and concepts of psychosomatic interaction, in relation to Greek philosophical thought. Part Three studies the reception of Hippocratic medicine, especially medical ethics and the theory of the four humours, in Galen and in late antiquity.